2017
DOI: 10.1186/s12977-017-0352-7
|View full text |Cite
|
Sign up to set email alerts
|

Interference of retroviral envelope with vaccine-induced CD8+ T cell responses is relieved by co-administration of cytokine-encoding vectors

Abstract: BackgroundRetroviral envelope (Env) proteins are known to exhibit immunosuppressive properties, which become apparent not only in retroviral infections, but also in gene-based immunizations using retroviral immunogens, where envelope interferes with the induction of CD8+ T cell responses towards another, simultaneously or subsequently delivered, immunogen.ResultsIn the Friend retrovirus mouse model, immunization with a plasmid encoding the Friend murine leukemia virus (F-MuLV) Leader-Gag protein resulted in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…However, we have shown that the GagL 85-93 epitope is rather weak and can be sub-dominant to vector-derived epitopes [45], which might result in impaired GagL 85-93 -specific CD8 + T cell responses in the MCMV background. We have also shown before that Env suppresses CD8 + T cell responses to simultaneously or subsequently administered immunogens [40, 46]; interestingly, we did not observe a suppressive effect of Env on MCMV-specific CD8 + T cell responses, so it would be intriguing to see if CD8 + T cell responses that are suppressed in DNA or adenovirus-based immunization are also unaffected by Env in the MCMV background.…”
Section: Discussionsupporting
confidence: 49%
“…However, we have shown that the GagL 85-93 epitope is rather weak and can be sub-dominant to vector-derived epitopes [45], which might result in impaired GagL 85-93 -specific CD8 + T cell responses in the MCMV background. We have also shown before that Env suppresses CD8 + T cell responses to simultaneously or subsequently administered immunogens [40, 46]; interestingly, we did not observe a suppressive effect of Env on MCMV-specific CD8 + T cell responses, so it would be intriguing to see if CD8 + T cell responses that are suppressed in DNA or adenovirus-based immunization are also unaffected by Env in the MCMV background.…”
Section: Discussionsupporting
confidence: 49%
“…As DBP 418 -426 did not have a dominance effect over GagL 85-93 and the dominance of hexon 486 -494 was lost in the C57BL/6 H-2D b/b background, we enquired next whether C57BL/6 mice would actually show responsiveness toward an Addelivered native leader-Gag. While we had performed immunization experiments in C57BL/6 mice in the past, in those experiments we had employed a mixture of the leader-Gag vector with an envelope-encoding vector (11), which we later showed to interfere with CD8 ϩ T cell induction (11,26). We immunized C57BL/6 mice once with Ad5.Leader-Gag, or with Ad5.Leader-Gag C1K as a positive control, and analyzed the GagL 85-93 -specific CD8 ϩ T cell response 2 weeks later by MHC I tetramer staining.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Liu and colleagues also tested genetic adjuvants, specifically DNA-encoded Flt3L and MIP-1α, and found that either electroporation or inclusion of genetic adjuvants can both increase immunogenicity of the DNA vaccine separately, but if electroporation was applied after the injection of the adjuvants, an additive effect was barely detectable [61]. However, this might not rule out that adjuvants addressing other pathways might possess better immunostimulatory potentials in DNA electroporation [62,63] or that the adjuvants might have greater impact in immunizations with immunosuppressive antigens [64].…”
Section: Plos Onementioning
confidence: 99%